IMPLEMENTASI PERATURAN DAERAH NOMOR 6 TAHUN 2017 TERHADAP PENERTIBAN HEWAN TERNAK DI KABUPATEN PANGKAJENE DAN KEPULAUAN - Astari, Alfira Nurfasihah; Hasan, Hamzah; Suriyadi, Suriyadi (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2023)
Regional government affairs are organized using the principle of autonomy. Regional governments have roles and strategies in fostering and supervising their regions, especially in the preparation and implementation of regional regulations. This study aims to find out how the Implementation of Regional Regulation Number 6 of 2017 Article 18 Paragraph 2 regarding the Control of Livestock. This type of research uses a qualitative field research method with an empirical juridical and normative syar'i approach. The results of this study indicate that the Implementation of Regional Regulation Number 6 of 2017 Article 18 Paragraph 2 on the Control of Livestock has not been running effectively and efficiently. As for several factors of the ineffectiveness of Regional Regulation No. 6 of 2017 include the lack of socialization provided by the government, lack of legal awareness, lack of firmness from law enforcement, and the absence of availability of land owned by breeders.